ANALISIS PENCAPAIAN PENDEWASAAN USIA PERKAWINAN DI KECAMATAN PANCURBATU KABUPATEN DELI SERDANG TAHUN 2015 - Zuraidah Zuraidah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2016)
Introduction: Some factors which can influence the acceleration or postponement of marriage in young age, among others, are knowledge, attitude, socio-cultural condition and custom, education, and socio-economic environment. The objective of the research was to find out and to analyze the coverage of bringing to adulthood of marriageable age in Pancur Batu Subdistrict, Deli Serdang District, in 2015. Method: The research used mixed methods (quantitative and qualitative). The population was 15,481 productive-aged women listed in Pancur Batu Subdistrict, in 2014. The samples were 120 productive-aged women who had married and listed in Pancur Batu Subdistrict, in 2014, taken by using proportional random sampling technique. The data were gathered by distributing questionnaires and analyzed by using multiple logistic regression analysis at α = 5%. Result: 55.8% of the respondents got married before they were 20 years old in Pancur Batu Subdistrict. Statistically, the variable which had the most dominant influence was adolescent intercourse at the coefficient regression value of 3.982. The result of the interviews showed that most of the informants stated that adolescence intercourse was the cause of getting marriage in young age. It is recommended that the related party should increase counseling about marriage in young age, increase bringing to adulthood of marriageable age through Center of Reproductive Health Counseling and Information and Adolescent Family Development in the subdistrict, and establish teenager organization as the means of their activities so that they will not be fallen into promiscuity. Parents and teenagers should increase their knowledge of reproductive health in order to prevent them from marriage in young age. Keywords: Marriage in young age, marriage age, adolescent intercourse